Reading-swimming: the sprinkling of introspection and amniotic pleasure in the poetry of Alicia Genovese - Prado Campos, Nadia (Revista Chilena de Literatura, 2020)
The following article is a reading of the collection of poems Aguas, by Alicia Genovese, which writes the memory of water and of the Argentinian dictatorship, and whose gravitational in-between and reflexive drizzle strokes with the swimmers of the poem towards the past. Subjective haul and a resonance chamber of subjectivity that destabilizes identity and prefigures the persistent act of thinking about the absent ones, exposing historic memory through the notion of water that becomes «the sprinkling of introspection» and the rhythm of remembrance, that, as amniotic pleasure, allows water and thought to breathe and to rewrite, in its itinerary towards the past, individual and collective memory that endures as an image that presents and recovers the geological layers of memory, projecting in the poem and beyond itself, as a poetics of complementarity and mutuality.